2021
DOI: 10.1186/s13148-021-01008-6
|View full text |Cite
|
Sign up to set email alerts
|

BRD4 inhibition alleviates mechanical stress-induced TMJ OA-like pathological changes and attenuates TREM1-mediated inflammatory response

Abstract: The aim of this paper was to investigate the protective effects of bromodomain containing 4 (BRD4) inhibition on the temporomandibular joint osteoarthritis (TMJ OA) induced by compressive mechanical stress and to explore the underlying mechanism. In vivo, a rat model of TMJ compressive loading device was used and BRD4 inhibitor was injected into the TMJ region. HE staining and micro-CT analysis were used for histological and radiographic assessment. Immunohistochemistry and qPCR were performed to detect inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 44 publications
0
15
0
Order By: Relevance
“…For bone disease, increased BRD4 also mediates the inflammatory reactions and aberrant proliferation of cells [ 21 ]. BRD4 has been confirmed as a promising therapeutic target for osteoarthritis, and decreased BRD4 could effectively improve the inflammatory stress in osteoarthritis [ 22 ]. Moreover, this study also confirmed that BRD4 could effectively reverse the effects of miR-129-5p on RA-FLSs.…”
Section: Discussionmentioning
confidence: 99%
“…For bone disease, increased BRD4 also mediates the inflammatory reactions and aberrant proliferation of cells [ 21 ]. BRD4 has been confirmed as a promising therapeutic target for osteoarthritis, and decreased BRD4 could effectively improve the inflammatory stress in osteoarthritis [ 22 ]. Moreover, this study also confirmed that BRD4 could effectively reverse the effects of miR-129-5p on RA-FLSs.…”
Section: Discussionmentioning
confidence: 99%
“… 45 In addition, it was reported that excessive mechanical stress increased the binding of BRD4 to H3K27ac on the promoter region of Trem1, leading to TMJ OA-like pathological changes. 46 These findings provided evidences for targeting BRD4 as a promising strategy for OA therapy. In the present study, we explored the potential epigenetic regulation mechanism during aberrant force-induced OA.…”
Section: Discussionmentioning
confidence: 82%
“…The chondrocyte nucleus was blue and other tissues were pink. For detecting p-NF-κB expression in the cartilage, immunohistochemistry was carried out according to the previous study [ 21 ]. The primary antibody was the Anti-Rabbit NF-kB p65 (phospho S276) antibody (ab194726, Abcam) and the secondary antibody is Goat Anti-Rabbit IgG H&L (HRP) (ab205718, Abcam).…”
Section: Methodsmentioning
confidence: 99%